2011
DOI: 10.24200/tjer.vol8iss1pp19-27
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Possible Seasonal Trends in Mortality Rate in Relation to Age, Gender and Environmental Conditions in Kuwait: A Preliminary Analysis

Abstract: Inherently, Kuwait a high frequency of dusty events through out the year due to its arid climate. Particulate air pollution has been linked to increased mortality due to various illnesses. For the purpose of improving health services, it is important to develop/establish an empirical basis for the possible link between mortality and air quality. In this paper, we examined mortality rates in Kuwait in relation to age, sex and dust episodes during a five-year period. Each year was divided into four seasons to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…A study conducted by Thalib and Al-Taiar [24] concluded that dust storms had a significant impact on asthma and respiratory hospital admissions. Al-Rifaia et al [37] and Al-Taiar and Thalib [5] showed that dust storms had little impact on short-term respiratory, cardiovascular or all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Thalib and Al-Taiar [24] concluded that dust storms had a significant impact on asthma and respiratory hospital admissions. Al-Rifaia et al [37] and Al-Taiar and Thalib [5] showed that dust storms had little impact on short-term respiratory, cardiovascular or all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%
“…One study measured ETS (Abdualrasool et al, 2018), 4 studies measured dust (Achilleos et al, 2019, Al-Rifaia et al, 2011, Al-Taiar and Thalib, 2014, Thalib and Al-Taiar, 2012; only 1 study did not found a significant correlation between exposure to dust and mortality, which contradict the findings in (Achilleos et al, 2019, Al-Taiar andThalib, 2014). 2 studies measured PM2.5 (Al-Hemoud et al, 2019b, Al-Hemoud et al, 2018; where the first one found that PM2.5 is have an effect on mortality correlated to Ischaemic heart disease and stroke; and morbidity correlated to respiratory problems respectively.…”
Section: Measured Pollutantsmentioning
confidence: 86%
“…Majority of the included 85 studies were non-epidemiological studies, only 8 studies were related to epidemiological studies, 4 on morbidity (Abdualrasool et al, 2018, Al-Hemoud et al, 2019b, Alsaber et al, 2020, Thalib and Al-Taiar, 2012 and 5 on mortality (Achilleos et al, 2019, Al-Hemoud et al, 2019b, Al-Hemoud et al, 2018, Al-Rifaia et al, 2011, (1 study assesses both morbidity, and mortality related to respiratory and cardiovascular and PM2.5 (Al-Hemoud et al, 2019b)), between the 5 mortality studies, only 1 study found no correlation between air pollution and mortality (Al-Rifaia et al, 2011). only 1 study assessed asthma which consider as major health problem in Kuwait (Khadadah, 2012), and it was from 1996-2000 to study dust effect (Thalib and Al-Taiar, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Previous pollution and health studies in Kuwait relied on large particulate matter (PM 10 ) [ 14 ], low visibility [ 15 ] and seasonal dust trends [ 16 ] as a proxies for air pollution, or respiratory hospital admissions as an upstream health outcome [ 17 , 18 ]. In this paper, we employed a previously developed model that estimated historically resolved fine particulate matter in the dusty environment of Kuwait, allowing us to more comprehensively assess its impact on mortality.…”
Section: Introductionmentioning
confidence: 99%